Thermomagnetic conversion of low-grade waste heat into electrical power. Issue 3 (September 2016) - Achkar, G El; Dianoux, A; Kheiri, A; Maillet, D; Mazet, T; Colasson, S; Feidt, M; Rado, C; Servant, F; Paul-Boncour, V
Abstract: A theoretical study relying on the thermal modelling of a Curie wheel, used for the conversion of low-grade waste heat into electrical power, is presented in this paper. It allows understanding the thermal behaviour of a Curie wheel operating in steady state in order to optimise its design. To this end, a stationary one-dimensional analytical thermal model, based on a Lagrangian approach, was developed. It allows determining the local distribution over time of the temperature in the magnetocaloric material exposed to a periodic sinusoidal heat source. Thanks to this model, the effects of different parameters (nature of the magnetocaloric material, nature and temperature of the fluid) were highlighted and studied.